Oligodendrocyte differentiation of induced pluripotent stem cells derived from subjects with schizophrenias implicate abnormalities in development - McPhie, Donna L.; Nehme, Ralda; Ravichandran, Caitlin; Babb, Suzann M.; Ghosh, Sulagna Dia; Staskus, Alexandra; Kalinowski, Amy; Kaur, Rupinderjit; Douvaras, Panagiotis; Du, Fei; Ongur, Dost; Fossati, Valentina; et al. (Translational psychiatry, 2018)
Abnormalities of brain connectivity and signal transduction are consistently observed in individuals with schizophrenias (SZ). Underlying these anomalies, convergent in vivo, post mortem, and genomic evidence suggest abnormal oligodendrocyte (OL) development and function and lower myelination in SZ. Our primary hypothesis was that there would be abnormalities in the number of induced pluripotent stem (iPS) cell-derived OLs from subjects with SZ. Our secondary hypothesis was that these in vitro abnormalities would correlate with measures of white matter (WM) integrity and myelination in the same subjects in vivo, estimated from magnetic resonance imaging. Six healthy control (HC) and six SZ iPS cell lines, derived from skin fibroblasts from well-characterized subjects, were differentiated into OLs. FACS analysis of the oligodendrocyte-specific surface, glycoprotein O4, was performed at three time points of development (days 65, 75, and 85) to quantify the number of late oligodendrocyte progenitor cells (OPCs) and OLs in each line. Significantly fewer O4-positive cells developed from SZ versus HC lines (95% CI 1.0: 8.6, F 1,10 = 8.06, p = 0.02). The difference was greater when corrected for age (95% CI 5.4:10.4, F 1,8 = 53.6, p < 0.001). A correlation between myelin content in WM in vivo, estimated by magnetization transfer ratio (MTR) and number of O4-positive cells in vitro was also observed across all time points (F 1,9 = 4.3, p = 0.07), reaching significance for mature OLs at day 85 in culture ( r = 0.70, p < 0.02). Low production of OPCs may be a contributing mechanism underlying WM reduction in SZ.